2014
DOI: 10.1051/0004-6361/201323075
|View full text |Cite
|
Sign up to set email alerts
|

A state-of-the-art analysis of the dwarf irregular galaxy NGC 6822

Abstract: We present a detailed photometric study of the dwarf irregular galaxy NGC 6822 aimed at investigating the properties of its stellar populations and, in particular, the presence of stellar radial gradients. Our goal is to analyse the stellar populations in six fields, which cover the whole bar of this dwarf galaxy. We derived the quantitative star formation history (SFH) of the six fields using the IAC method, involving IAC-pop/MinnIAC codes. The solutions we derived show an enhanced star formation rate (SFR) i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…); however, the same explanation seems not to be valid for the intermittent bursts of SFH seen in the past 1-2 Gyr in these galaxies, though those events are less strong than the older star forming events. Fusco et al (2014) determined the SFH of NGC 6822 in 6 fields at different distances from the centre, out to 4 kpc. Their shapes differ significantly from each other and there is no unambiguous signature of a drop at a common time.…”
Section: Relation To the Milky Waymentioning
confidence: 99%
“…); however, the same explanation seems not to be valid for the intermittent bursts of SFH seen in the past 1-2 Gyr in these galaxies, though those events are less strong than the older star forming events. Fusco et al (2014) determined the SFH of NGC 6822 in 6 fields at different distances from the centre, out to 4 kpc. Their shapes differ significantly from each other and there is no unambiguous signature of a drop at a common time.…”
Section: Relation To the Milky Waymentioning
confidence: 99%
“…The SFH of NGC 6822 will be presented by using LPV stars as a tracer of the SFH of the galaxy. Figure 1, left panel, shows the CMD which is over-plotted isochrones by Marigo et al (2017) with a distance modulus of 23.51 ± 0.051 mag and interstellar extinction of A V = 0.77 (Whitelock et al, 2013), and also Z = 0.0007 based on the result of Fusco et al (2014), who is reported in a range of 0.0001 < Z < 0.01.…”
Section: Discussion and On-going Workmentioning
confidence: 99%
“…Previous studies (e.g. Fusco et al 2014) yielded evidence that there are stars older than 10 Gyr in NGC 6822. Based on the presence of the old stellar populations, the observed values of gas-phase oxygen abundance and gas mass fraction are compared to predicted values in the universe at present (t = 13.80 Gyr).…”
Section: Chemical Evolution Modelsmentioning
confidence: 95%